ANALYSIS OF SOCIAL FORESTRY BUSINESS MANAGEMENT IN FOREST MANAGEMENT UNIT (FMU) REGION I STABAT LANGKAT REGENCY - Zumar Halim Rambe; Oding Affandi; Delvian Delvian (RADJA PUBLIKA, 2025)
Social forestry is a program that provides legal access for communities to manage forests in a sustainable manner to improve economic welfare while maintaining environmental sustainability. Forest Management Unit (FMU) Region I Stabat, Langkat Regency has Social Forestry Group (SFG) that successfully rehabilitated 3436 ha of mangrove forest in 2021 [1], but business development has not been managed optimally [2], [3]. This study aims to analyze the business model of social forestry business development with the Business Model Canvas (BMC) approach and analyze the business development strategies needed in developing social forestry businesses in FMU Region I Stabat[4]. The study was conducted on four SFG: KSU Bahagia Keluarga Bahari, KTH Mekar, KT Peduli Pesisir and LPHD Pasar Rawa. Data were obtained through observations, interviews, and literature studies with an analytical descriptive approach [5]. The results showed that BMC at the blue level Social Forestry Business Group (SFBG) needs to create a value prosposition so that the business has marketable products through improving the elements of key activities, key resources and cooperation with key partners [3]. Improvement at the gold level SFBG requires efforts to increase the customer segment element which is done by increasing the value proposition, customer relationship, and channels elements so that business products can be marketed to national, regional, and international consumers [3], [6]. Business development strategies are carried out with product diversification strategies, strengthening partnerships, and optimizing digital marketing to improve business efficiency and sustainability [7]. Thus, social forestry business in FMU Region I Stabat has good prospects, but requires further support in terms of capital, market access, and human resource capacity development [8].